2011
DOI: 10.1002/smll.201100005
|View full text |Cite
|
Sign up to set email alerts
|

A Dithienosilole‐Benzooxadiazole Donor–Acceptor Copolymer for Utility in Organic Solar Cells

Abstract: A systematic evaluation of a novel conjugated polymer, bearing alkyl side chains on both the donor and acceptor units, is conducted using nanoscale characterization techniques and device fabrication. How to manage the use of solvent additives to achieve power‐conversion efficiencies of up to 3.7% is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…2,1,3-Benzoxadiazole (BO) has been widely utilized as an electron-deficient unit to construct alternating D-A polymers for polymer BHJ solar cells, and the replacement of the BT acceptor with the more electronegative BO acceptor leads to decreases in the energy levels of frontier orbitals and hence increases in the open-circuit voltage (V oc ) of the corresponding devices. [39][40][41] On the other hand, the 2,1,3-benzoselenodiazole (BS) acceptor has also shown great promise as a building block for the development of photovoltaic materials as BS-containing systems generally have smaller optical bandgaps than their BTbased counterparts. [42][43][44][45] Along these lines, we report here the synthesis of four D-A-A molecular donors that bear BO…”
Section: Introductionmentioning
confidence: 99%
“…2,1,3-Benzoxadiazole (BO) has been widely utilized as an electron-deficient unit to construct alternating D-A polymers for polymer BHJ solar cells, and the replacement of the BT acceptor with the more electronegative BO acceptor leads to decreases in the energy levels of frontier orbitals and hence increases in the open-circuit voltage (V oc ) of the corresponding devices. [39][40][41] On the other hand, the 2,1,3-benzoselenodiazole (BS) acceptor has also shown great promise as a building block for the development of photovoltaic materials as BS-containing systems generally have smaller optical bandgaps than their BTbased counterparts. [42][43][44][45] Along these lines, we report here the synthesis of four D-A-A molecular donors that bear BO…”
Section: Introductionmentioning
confidence: 99%
“…They have modified the SDTBO copolymer, i.e. SDTBO1 , by increasing the alkyl side chain on both donor and acceptor units and found that increasing the number of alkyl side chains helps in breaking up the intermolecular aggregates and increases the solubility in organic solvents . The BHJ organic solar cell using SDTBO1 :PC 71 BM blend (cast from chlorobenzene) shows PCE of 1.6%, which has been further improved up to 3.7% when 4% of di‐iodooctane (DIO) is added to the chlorobenzene (CB).…”
Section: Low Band Gap Copolymer Based Bhj Solar Cellsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In addition to solid state structure, it is well known that the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels are critical for device performance. [9][10][11][12][13] Extensive monomer modication has been undertaken in order to tune energy levels and solid state structures, including: extending the conjugation of the polymer repeat unit, 14,15 single atom substitution in one or both of the donor and acceptor monomers, [16][17][18][19][20][21][22] and monomer side chain substitution. 23,24 Recently, single atom substitution has gained increasing attention because polymer properties may be predictably tuned through modular chemistry.…”
Section: Introductionmentioning
confidence: 99%